2020
DOI: 10.1016/j.immuni.2020.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Second-Strand Synthesis-Based Massively Parallel scRNA-Seq Reveals Cellular States and Molecular Features of Human Inflammatory Skin Pathologies

Abstract: Summary High-throughput single-cell RNA-sequencing (scRNA-seq) methodologies enable characterization of complex biological samples by increasing the number of cells that can be profiled contemporaneously. Nevertheless, these approaches recover less information per cell than low-throughput strategies. To accurately report the expression of key phenotypic features of cells, scRNA-seq platforms are needed that are both high fidelity and high throughput. To address this need, we created Seq-Well S … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
220
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 202 publications
(226 citation statements)
references
References 100 publications
6
220
0
Order By: Relevance
“…To investigate how immune responses vary between different severities of COVID-19, we profiled peripheral blood immune cells from 64 patients with COVID-19 and 12 healthy controls with three high-dimensional single-cell modalities: Seq-Well (28,29)-based scRNA-seq (33 patients, 8 controls; including 7 patients previously profiled by our group (15)), scATAC-seq (18 patients, 7 controls), and CyTOF (64 patients, 12 controls; Fig. 1A, Fig.…”
Section: A Trimodal Single-cell Atlas Of the Peripheral Immune Responmentioning
confidence: 99%
“…To investigate how immune responses vary between different severities of COVID-19, we profiled peripheral blood immune cells from 64 patients with COVID-19 and 12 healthy controls with three high-dimensional single-cell modalities: Seq-Well (28,29)-based scRNA-seq (33 patients, 8 controls; including 7 patients previously profiled by our group (15)), scATAC-seq (18 patients, 7 controls), and CyTOF (64 patients, 12 controls; Fig. 1A, Fig.…”
Section: A Trimodal Single-cell Atlas Of the Peripheral Immune Responmentioning
confidence: 99%
“…However, for detecting non-mRNA sequences, such as short micro RNA or antibody-attached oligonucleotides (Stoeckius et al, 2017), UMI-encoded HDMI-array could be more useful in the future. UMI-encoded HDMI-array could also enable tagmentation of the mRNA library, which could increase the diversity of the transcriptome read sequences (Hughes et al, 2020; Stickels et al, 2020). UMI encoding of the HDMI-array could be achieved by various methods, including oligonucleotide ligation (Vickovic et al, 2019) or template-based extension (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Recent discoveries have demonstrated that fibroblasts also play an active role in tissue inflammation. Following injury, fibroblasts contribute to early inflammatory pathogen and damage responses in numerous tissues, such as skin, lung, liver, intestines, heart, conjunctiva, urogenital tract and adipose tissue [ 94 , 95 , 96 , 97 , 98 ]. These pro-inflammatory fibroblasts contribute to the immune response, frequently through the recruitment and activation of myeloid cells.…”
Section: Contribution Of Fibroblasts To Injury-induced Inflammatiomentioning
confidence: 99%